A bookend in the Arisaema japonicum (Araceae) taxonomic debate: morphological and genetic evidence for synonymization - Scholten, Justin; Sprenger, Arianna; Hullihen, Olivia; Specht, Chelsea D. (Phytotaxa, 2025)
The taxonomic distinction between Arisaema japonicum and A. serratum has long been contentious, with treatments alternating between recognizing them as distinct species or conspecific variants. To resolve their taxonomic status, we conducted an integrative species delimitation analysis combining detailed morphological assessments with genome-wide single nucleotide polymorphism (SNP) data. Morphological investigations revealed continuous trait variation with numerous intermediates, precluding discrete morphological classification. Coalescent-based phylogenetic inference using Singular Value Decomposition Scores (SVDquartets) failed to recover A. japonicum as a monophyletic group, and principal component analysis of SNP data showed no genetic clustering corresponding to species boundaries. Species delimitation using Bayes Factor Delimitation (BFD) overwhelmingly supported a single-species model over competing hypotheses, including those based on previous morphological classifications. Together, these results indicate that A. japonicum does not represent a distinct evolutionary lineage and is best treated as conspecific with A. serratum. Our findings reconcile morphological and genetic data, providing strong support for the synonymization of A. japonicum under A. serratum, thereby resolving a longstanding taxonomic ambiguity within the genus Arisaema.